Identifikasi Drug Related Problems (DRPs) Pada Kasus Diare Anak Pasien Rawat Jalan di UPT. Puskesmas X Kudus - Setyoningsih, Heni; Latifah, Siti Nor; Adiningsih, Retnowati; Wijaya, Hasty Martha (Jurnal Farmasi & Sains Indonesia, 2024)
Diarrhea is still a health problem in developing countries, including Indonesia. Diarrhea is a potential endemic disease of Extraordinary Events (KLB) accompanied by death that often occurs in Indonesia. Drug Related Problems (DRPs) are unwanted events experienced by patients and actually or potentially interfere with the desired therapeutic results. This study aims to determine Drug Related Problems (DRPs) including drug selection, drug form, dose selection, duration of treatment and drug interactions in cases of diarrhea in outpatients at UPT. X Kudus District Health Center for the period January - June 2020. Non-experimental research with observational methods conducted by collecting data retrospectively and analyzed descriptively quantitatively. The sampling technique used was total population sampling by purposive sampling with clear and complete inclusion criteria for outpatient medical records with a diagnosis of diarrhea aged 0-11 years at UPT. X Kudus District Health Center for the period January - June 2020. The results of the study obtained 79 patients who met the inclusion criteria. This study showed that the most common types of DRPs were drug interactions (12%), drug selection (10%), and dose selection (8%). The amount of drug use did not significantly affect the incidence of DRPs in the drug interaction category (P = 0.019). The results showed that there had been DRPs in pediatric diarrhea patients at UPT. X Kudus District Health Center for the period January - June 2020.